La famille choisie toujours d’actualité ? Vers une diversification des formes de liens familiaux pour les minorités sexuelles et de genre au Québec - Marianne Chbat; Geneviève Pagé; Isabel Côté; Martin Blais (Genre, Sexualité et Société)
A chosen family can be defined as a collection of individuals with whom a person maintains relationships based on trust and solidarity (Weeks, Heaphy & Donovan, 2011). More specifically, these links are manifested in particular through lasting material or emotional support between at least two individuals who mutually grant each other a preponderant place in their respective lives without necessarily being in a romantic relationship or even without being biologically linked (Weston, 1997). While many sexual and gender minorities do not always obtain recognition or support from their original or biological family, the chosen family is of particular importance to LGBTQ+ people (Doucet & Chamberland, 2020). Based on biographical interviews conducted with 94 people who participated in the SAVIE-LGBTQ project (SSHRC 2016-2023), this article will highlight the irrevocable place that the chosen family still occupies today for many people who identify themselves as sexual or gender minorities. The chosen family has been historically important in the life trajectories of many LGBTQ+ people who have evolved in a social and legal context where they suffered a lot of discrimination. However, despite the increasingly favorable inclusion of LGBTQ+ communities within Québec customs, the chosen family still acts today as a support and safety net for the majority of people who identify with these communities, regardless of their age. Indeed, the chosen family always seems to meet the emotional and material needs for several sexual and gender minorities. This qualitative analysis approaching the life course (Elder, 1995) as a theoritical framework will allow us to shed light on the ways in which the chosen family still promotes a more positive and assumed identity assertion for LGBTQ+ people and how it occupies a particularly significant place for LGBTQ+ multi-marginalized people such as racialized or migrant LGBTQ+ people or trans people and older people.